Financial Incentives: Only One Piece of the Workplace Wellness Puzzle; Comment on "Corporate Wellness Programs: Implementation Challenges in the Modern American Workplace" - Kristin Van Busum; Soeren Mattke (Kerman University of Medical Sciences, 2013)
In this commentary, we argue that financial incentives are only one of many key components that employers should consider when designing and implementing a workplace wellness program. Strategies such as social encouragement and providing token rewards may also be effective in improving awareness and engagement. Should employers choose to utilize financial incentives, they should tailor them to the goals for the program as well as the targeted behaviors and health outcomes.